Diagnostic hearing tests - EW, Johnson (Journal of All India Institute of Speech and Hearing)
Diagnostic hearing tests are especially important in the differential diagnosis of cochlear versus retrocochlear lesions. The typical diagnostic test battery consists of pure tone audiometry, loudness function tests, and SISI tests, speech discrimination tests, and tone decay tests (Bakesy and tone decay).